2019
DOI: 10.3390/ijerph16173086
|View full text |Cite
|
Sign up to set email alerts
|

Body Changes and Decreased Sexual Drive after Dialysis: A Qualitative Study on the Experiences of Women at an Ambulatory Dialysis Unit in Spain

Abstract: Chronic kidney disease (CKD) has considerable effects on the quality of life of patients, impairing everyday activities and leading to lifestyle changes, as well as affecting body image and intimate relationships. Our aim was to describe the experience of female patients with CKD at an ambulatory dialysis unit regarding body changes and sexuality. A qualitative phenomenological study exploring how 18 female patients, treated at the dialysis unit of a Spanish hospital, perceived their sexuality and intimate rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
2
9
0
4
Order By: Relevance
“…The current study showed that social life complexities like marital relationship disturbance contribute to separation, segregation, and stigma by communities and even families. This finding is supported by a study conducted in Spain [ 28 ]. On the other hand, the current study showed that most participants have a strong religious base which is articulated in the belief that the treatment they obtain in the HD center was blessed by God, resonating with a study from Jordan [ 29 ].…”
Section: Discussionsupporting
confidence: 82%
“…The current study showed that social life complexities like marital relationship disturbance contribute to separation, segregation, and stigma by communities and even families. This finding is supported by a study conducted in Spain [ 28 ]. On the other hand, the current study showed that most participants have a strong religious base which is articulated in the belief that the treatment they obtain in the HD center was blessed by God, resonating with a study from Jordan [ 29 ].…”
Section: Discussionsupporting
confidence: 82%
“…8,9,16 Indivíduos com DRC têm dificuldade para estabelecer e/ou manter o emprego devido ao tempo que passam em TRS, e sofrem de comprometimento físico e sintomas como fraqueza, cansaço, distúrbios de sono, falta de ar, tontura e mal-estar, que por sua vez afetam o desempenho das atividades da vida diária e produzem efeitos psicológicos e sofrimento emocional. 8,10,17 Portadores da doença e os familiares muitas vezes têm percepções e desejos muito semelhantes, nomeadamente evitar a dor e minimizar o sofrimento. As pessoas frequentemente compartilham experiências passadas de morte, e a exploração dessas experiências pode facilitar uma compreensão mais profunda dos desejos e medos.…”
Section: Resultsunclassified
“…Kidney transplant recipients go through a prolonged period of adaptation to disease, which involves several body changes [37]. The use of kidney replacement therapies such as dialysis before the transplant provokes important changes in body image due to uremia effects and the creation of the dialytic access [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplant recipients go through a prolonged period of adaptation to disease, which involves several body changes [37]. The use of kidney replacement therapies such as dialysis before the transplant provokes important changes in body image due to uremia effects and the creation of the dialytic access [37,38]. Furthermore, the integration and adaptation of a new kidney into the body implies an adjustment of body image, which can influence intimacy and sexual behaviors [39].…”
Section: Discussionmentioning
confidence: 99%